Strain engineering of industrial strains by using randomized libraries of transcription factor (biofuel-1-propanol). - Yong, Wai Wan. (2010)
In the modern society, fuel and other energy forms have been some of the most important commodities driving the economy. This project addresses the concerns of biofuel by investigating the possibility of obtaining Escherichia coli mutants on the cAMP regulatory protein (CRP) gene which is one of the seven global transcription factors controlling various phenotypes of the bacteria including the phenotype of interest – tolerance of growth in 1-propanol. A randomized library of this particular portion of gene is generated via directed evolution technique, particularly error-prone Polymerase Chain Reaction (ep-PCR). The mutants are then ligated into the plasmid and transformed into the cells. A selection criterion is established based on the concentration of 1-propanol that half of the wild type E. coli cells can survive in. Based on that, the mutants are then identified out in the selection steps carried out after ep-PCR. The successful mutants are grown and the growth curve is plotted out giving a confirmation that the mutant indeed has better tolerance against the wild type. The sequencing of mutant gene is then done by external laboratory. Three mutants are obtained from this experiment with a total of five mutations. Based on the structure of CRP from past literature data, the mutation results are discussed and reasons postulated. The limitations of the project are discussed with the potential of future development explored. Finally, the project is concluded with the objectives met.